2013
DOI: 10.1016/s0140-6736(13)60771-0
|View full text |Cite
|
Sign up to set email alerts
|

John Snow's legacy: epidemiology without borders

Abstract: This Review provides abstracts from a meeting held at the London School of Hygiene and Tropical Medicine, on April 11–12, 2013, to celebrate the legacy of John Snow. They describe conventional and unconventional applications of epidemiological methods to problems ranging from diarrhoeal disease, mental health, cancer, and accident care, to education, poverty, financial networks, crime, and violence. Common themes appear throughout, including recognition of the importance of Snow’s example, the philosophical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 47 publications
(48 reference statements)
0
23
0
3
Order By: Relevance
“…His perseverance and meticulous investigation of the Broad Street cholera epidemic is generally viewed as an important milestone in the evolution of epidemiology as a core specialty of global health. 16,17 In 1852, cholera spread east to Indonesia and was later carried to China and Japan in 1854. Also in 1854, an outbreak of cholera in Chicago took the lives of 5.5% of the population (about 3500 people).…”
Section: Cholera Pandemicsmentioning
confidence: 99%
“…His perseverance and meticulous investigation of the Broad Street cholera epidemic is generally viewed as an important milestone in the evolution of epidemiology as a core specialty of global health. 16,17 In 1852, cholera spread east to Indonesia and was later carried to China and Japan in 1854. Also in 1854, an outbreak of cholera in Chicago took the lives of 5.5% of the population (about 3500 people).…”
Section: Cholera Pandemicsmentioning
confidence: 99%
“…13 Lifestyle-associated health issues, including tobacco use and alcohol consumption, as well as the lack of implementation of prevention strategies among the migrant communities may also importantly affect the long-term consequences of movement between locations with different health determinants. 12,14,15 Early studies performed mainly in Great Britain and the Netherlands revealed an increased risk of type 2 diabetes, hypertension [16][17][18] obesity and metabolic syndrome in some ethnic minority groups. Cultural reasons may obstacle the dissemination of prevention strategies among immigrants, and communication between healthcare providers and migrant clients remains poor.…”
Section: Introductionmentioning
confidence: 99%
“…The science of phylogeny, when applied to tracking an outbreak, has come a long way since Snow established the association between the Broad Street pump and the spread of cholera during the 1854 outbreak in London. 83 The technology of WGS has applied to studying the spread of drugresistant organisms in a single facility 84 and also to large-scale epidemiologic studies monitoring the evolution and spread of a pathogens over time. 85,86 Barriers to the widespread use of NGS in infection control include concerns regarding data quality and the efficient use of bioinformatics in clinical laboratories.…”
Section: Future Of Infection Control In the Molecular Eramentioning
confidence: 99%